1990
DOI: 10.1104/pp.92.3.602
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Boron Applications Increase the Final Number of Branches and Pods on Branches of Field-Grown Soybeans

Abstract: Our previous work demonstrated that boron (B) supplied to soybeans (Glycine max [L.] Merrill cv 'Williams 82') by a stem infusion technique increased the number of pods on branches and led to a significant yield increase. Therefore, research was continued to determine whether soil or foliar applications of B could be used to achieve the same results. Field experiments were completed with both soil and foliar applications of B. Only the foliar applications of B resulted in a significant increase in the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 20 publications
9
69
2
Order By: Relevance
“…Recently, it was found that FB increased nodule weight under irrigated greenhouse conditions [43]. The current results showed that, even though B concentration in leaves was above the critical level (20 mg B kg -1 , critical level of B in leaves for normal plant growth) [44], FB resulted in a positive effect on seed and nodule weights, agreeing with previous research of those of [7,43,45]. Our results showed that foliar B increased grain weight, nodule mass and number due to the stimulatory effects of B on growth and development [9,11] and nodule improvement.…”
Section: Effect Of B and Water Stress On Grain Weight Nodule Mass Ansupporting
confidence: 81%
See 3 more Smart Citations
“…Recently, it was found that FB increased nodule weight under irrigated greenhouse conditions [43]. The current results showed that, even though B concentration in leaves was above the critical level (20 mg B kg -1 , critical level of B in leaves for normal plant growth) [44], FB resulted in a positive effect on seed and nodule weights, agreeing with previous research of those of [7,43,45]. Our results showed that foliar B increased grain weight, nodule mass and number due to the stimulatory effects of B on growth and development [9,11] and nodule improvement.…”
Section: Effect Of B and Water Stress On Grain Weight Nodule Mass Ansupporting
confidence: 81%
“…This indicated that both B and NO 3 stimulated NR enzyme somehow, maybe by facilitating nitrate availability in the cytoplasm to NR for reduction or enhancing nitrate translocation from the vacuoles to the cytoplasm, leading to higher NRA activity. This hypothesis was supported by the effect of B ion uptake [2,16] and the direct or indirect effects of B on the plasma membrane bound H+ ATPase (plasmalemma H+-ATPase activity) [7,17], cell wall structure and membrane integrity [2,7]. Our results are supported by [2] in that B may have an indirect influence on nitrate uptake and assimilation, and enhance NRA by inducing nitrate availability and increasing protein de novo synthesis as a result of nitrate absorption [49].…”
Section: Effect Of B and Water Stress On Nitrogen Fixation And Nitrogmentioning
confidence: 62%
See 2 more Smart Citations
“…Wilczek and Ćwintal (2008) found no significant effect of foliar B application in red clover during the bud formation stage on inflorescence number per stem. Schon and Blevins (1990) reported significantly more branches per plant and pods per branch in soybean as the result of B application at the onset of intensive growth. These results suggest that the effect of foliar-applied B on certain yield components is dependent on plant development stage during the treatment.…”
Section: Resultsmentioning
confidence: 99%